The Use of Taxonomic Analysis in the Assessment of Immigrants Integration in the European Union - Cymbranowicz, Katarzyna Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
In recent years, as a result of numerous crises, including mainly the so‑called refugee and migration crisis in 2015–2016 and the crisis on the Polish-Belarusian and Polish-Ukrainian borders in 2021–2022, the scale and structure of migration processes in Europe, including in the Member States of the European Union, has changed significantly. It is worth emphasizing that from the very beginning this process attracted the attention of the media, which made the issues of migration, including the issues of integration and integration policy towards immigrants, the subject of discussions and disputes at various spaces. Given the above the article discusses the problem of the integration of immigrants residing in the territory of the Member States of the European Union. This phenomenon is subject to a taxonomic analysis, in which the subjective scope is limited to the Member States of the European Union and the time scope is limited to the last decade (2011–2021). The aim of the article is to answer the question to what extent the immigrant integration policy is integrative, ie. ‘open’. In order to achieve such research goal the results of research conducted by the European Commission in cooperation with Eurostat and the Migration Policy Group were used, and it was possible to carry out comparable statistical analyzes. The obtained results reflected the spatial approach to the similarity of the Member States of the European Union in terms of their ‘openness’ to immigrants in the last 10 years and the changes that took place during that time as a result of crisis situations caused by uncontrolled migratory movements to Europe.